Antibody blockade of IL-17 family cytokines in immunity to acute murine oral mucosal candidiasis. Issue 6 (1st June 2016) - Whibley, Natasha; Tritto, Elaine; Traggiai, Elisabetta; Kolbinger, Frank; Moulin, Pierre; Brees, Dominique; Coleman, Bianca M; Mamo, Anna J; Garg, Abhishek V; Jaycox, Jillian R; Siebenlist, Ulrich; Kammüller, Michael; et al.
Abstract : OPC requires IL-17R signaling in mice and humans; IL-17A, but not IL-17F blockade, predisposes to OPC, and functional redundancy among cytokines is evident. Abstract: Antibodies targeting IL-17A or its receptor, IL-17RA, are approved to treat psoriasis and are being evaluated for other autoimmune conditions. Conversely, IL-17 signaling is critical for immunity to opportunistic mucosal infections caused by the commensal fungus Candida albicans, as mice and humans lacking the IL-17R experience chronic mucosal candidiasis. IL-17A, IL-17F, and IL-17AF bind the IL-17RA-IL-17RC heterodimeric complex and deliver qualitatively similar signals through the adaptor Act1. Here, we used a mouse model of acute oropharyngeal candidiasis to assess the impact of blocking IL-17 family cytokines compared with specific IL-17 cytokine gene knockout mice. Anti-IL-17A antibodies, which neutralize IL-17A and IL-17AF, caused elevated oral fungal loads, whereas anti-IL-17AF and anti-IL-17F antibodies did not. Notably, there was a cooperative effect of blocking IL-17A, IL-17AF, and IL-17F together. Termination of anti-IL-17A treatment was associated with rapid C. albicans clearance. IL-17F-deficient mice were fully resistant to oropharyngeal candidiasis, consistent with antibody blockade. However, IL-17A-deficient mice had lower fungal burdens than anti-IL-17A-treated mice. Act1-deficient mice were much more susceptible to oropharyngeal candidiasis than anti-IL-17A antibody-treated mice, yet anti-IL-17A and anti-IL-17RA treatment caused equivalent susceptibilities. Based on microarray analyses of the oral mucosa during infection, only a limited number of genes were associated with oropharyngeal candidiasis susceptibility. In sum, we conclude that IL-17A is the main cytokine mediator of immunity in murine oropharyngeal candidiasis, but a cooperative relationship among IL-17A, IL-17AF, and IL-17F exists in vivo. Susceptibility displays the following hierarchy: IL-17RA- or Act1-deficiency > anti-IL-17A + anti-IL-17F antibodies > anti-IL-17A or anti-IL-17RA antibodies > IL-17A deficiency.